Proceedings of the Proceedings of the 4th Progressive and Fun Education International Conference, Profunedu 2019, 6-8 August 20 2019
DOI: 10.4108/eai.7-8-2019.2288422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students’ Difficulties in Solving Trigonometry Problems

Abstract: This study aimed to describe the difficulties of students in solving math problems, especially in solving trigonometry questions.. The subjects of this study were freshmen majoring math program who had already taken trigonometry courses. The research type was qualitative descriptive research. Data collection tools were essay trigonometry tests, deep interviews and documentation. Data analysis techniques were carried out using document analysis techniques. The results show that the students have difficulty in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
2
6
0
1
Order By: Relevance
“…While the research conducted by Meidina stated that students' errors in solving trigonometric problems were grouped into three categories, namely mathematical statements, conceptual errors, and calculation errors (Nurmeidina and Rafifiyah, 2019). This research that conducted has a difference with previous studies, namely the analysis of students' problemsolving abilities in mathematics lessons based on the Polya's stages which includes understanding the problem, planning problem solving, solving the problems based on the plan, and checking the process and the result.…”
Section: Introductionmentioning
confidence: 89%
“…While the research conducted by Meidina stated that students' errors in solving trigonometric problems were grouped into three categories, namely mathematical statements, conceptual errors, and calculation errors (Nurmeidina and Rafifiyah, 2019). This research that conducted has a difference with previous studies, namely the analysis of students' problemsolving abilities in mathematics lessons based on the Polya's stages which includes understanding the problem, planning problem solving, solving the problems based on the plan, and checking the process and the result.…”
Section: Introductionmentioning
confidence: 89%
“…Bezuidenhout (2001) also found that some problems and misconceptions in calculus could be a result of teaching methods which emphasises to a large extent, procedural aspects of the calculus and neglects a solid grounding in the underpinnings of calculus. From the results of the study, by Nurmeidina and Rafidiyah (2019) it was found that students revealed poor conceptual and procedural understanding of integration, and struggled with other topics required for integration, because of a poor background knowledge. Often, one of the reasons for students' poor performance in higher level mathematics is because of a limited background of the prerequisite concepts (Kazunga & Bansilal, 2020).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In line with this, the previous study from Maknum (2022) reveals that there are epistemological obstacles in learning trigonometry, which lead to the students' understanding of the trigonometry and trigonometry functions. Another finding from Nurmeidina denoted that in solving problem related to trigonometry, students are having lack of understanding in determine procedures to execute the problems and formulating mathematical sentences (Nurmeidina & Rafidiyah, 2019). Based on the existing findings, there are problems in learning trigonometry which make students feel that trigonometry is difficult to be learned.…”
Section: Introductionmentioning
confidence: 99%